Anglophone Literature in Second-Language Teacher Education : Curriculum Innovation Through Intercultural Communication - Quinn, Justin; Kleckova, Gabriela (Abingdon, Oxon ; New York, NY : Routledge, 2021)
Anglophone Literature in Second Language Teacher Education proposes new ways that literature, and more generally culture, can be used to educate future teachers of English as a second language. Arguing that the way literature is used in language teacher education can be transformed, the book foregrounds transnational approaches and shows how these can be applied in literature and cultural instruction to encourage intercultural awareness in future language educators. It draws on theoretical discussions from literary and cultural studies as well as applied linguistics and is an example how these cross-discipline conversations can take place, and thus help make Second-language teacher education (SLTE) programs more responsive to the challenges faced by future English-language teachers. Written in the idiom of literary scholarship, the book uses ideas of intercultural studies that have gained widespread support at research level, yet have not affected literature-cultural curricula in SLTE. As the first interdisciplinary study to suggest how SLTE programs can respond with curricula, this book will be of great interest for academics, scholars and post graduate students in the fields of applied linguistics, L2 and foreign language education, teacher education and post-graduate TESOL. It has universal appeal, addressing teaching faculty in any third-level institution that prepares language teachers and includes literary studies in their curriculum, as well as administrators in such organizations.
OCLC-licensed vendor bibliographic record.
Keywords: Language teachers -- Training of; EDUCATION / General; EDUCATION / Administration / General; EDUCATION / Language Experience Approach